Biomechanical analysis of ideal knee flexion angle for ACL graft tensioning utilizing multiple femoral and tibial tunnel locations. Issue 7 (30th July 2021) - Guth, Jared; Akhavan, Sam; Schimoler, Patrick; Miller, Mark; Hammarstedt, Jon
Objectives: Despite more anatomic reconstruction of the ACL, graft failure rate has been reported to be greater than 5% at 5 years. There is concern that anatomic reconstructions may not result in an isometric graft and may predispose the graft to stretching. The current biomechanical study evaluated excursion of the ACL with different drill points for both femoral and tibial tunnels. The purpose was to evaluate the excursion of the ACL with both anatomic and non-anatomic tunnel combinations and determine the optimal flexion angle to tension the ACL to minimize stretching of the graft during motion. Methods: Ten cadaveric knee specimens, mid-femur to mid-tibia, were dissected of skin and subcutaneous tissue. The ACL was sectioned and the femoral and tibial attachments were marked prior to excision. A 1/16 inch drill was used to create a tunnel in the center of the ACL footprint on the tibia and femur and additional tunnels were made 5mm from the original tunnel (Figure 1). A suture was passed through each tunnel combination (Femur A-F; Tibia A-E) and was attached to a string potentiometer. The knee was ranged from full extension to 120 degrees of flexion for 10 cycles while mounted in a custom fixture that measured angle of flexion in the sagittal plane. The change in length (excursion) of the suture during movement was recorded for each combination of femoral and tibial tunnels. Results: Anatomic reconstruction of the ACL with tunnel placement in the center of the femoral (femoral tunnel A) and tibial (tibial tunnel A) footprint did not result in an isometric graft, with excursion of the ACL during knee motion of 7.46mm (SD 2.7mm). The tunnel combination that resulted in the least amount of excursion during knee motion was a reconstruction with a femoral footprint 5mm anterior to the femoral (femoral tunnel D) and 5mm posterior to the tibial footprint (tibial tunnel D) (4.2mm, SD 1.37mm). The tunnel combination that resulted in the most amount of excursion during knee motion was utilized femoral footprint 5mm proximal to the femoral (femoral tunnel F) and 5mm posterior to the tibial footprint (tibial tunnel D) (9.81mm, SD 2.68mm). In an anatomic tunnel placement, we found the angle with the most excursion of the ACL to occur at 2.84 degrees of flexion (SD 4.22). Conclusions: Anatomic ACL reconstruction results in significant excursion of the ACL during range of motion. If not tensioned properly, the ACL can stretch during range of motion, potentially leading to re-rupture. In order to prevent stretching of the graft, the current biomechanical study recommends tensioning an anatomic ACL reconstruction at its point of maximal exertion, or about 10 degrees of flexion. We also determined optimal flexion angles for tensioning the ACL for tunnel combinations that may be non-anatomic. : :